The All Lithuanian Conference of 5 April 1943: the Lithuanian Political Elite on the Crossroads of Collaboration and Resistance - Zizas, Rimantas (Genocidas ir rezistencija, 2024)
This article describes the political events in Lithuania under German occupation in the spring of 1943, when, thanks to the unified resistance of Lithuanian society, the establishment of an SS legion was foiled and the German occupiers started repressions. The All Lithuanian Conference, which was supposed to explore the mutual objectives of Lithuanians and Germans in the pursuit of a solution for the critical and divisive situation, was convened in Kaunas on 5 April 1943.The purpose of the article is to describe and analyse the preparatory work for the conference, the views of various political forces, the moods dominant in society at that time, the procedure for the selection and composition of the conference participants, the difficult progress of the conference, the critique of the policies of the occupiers, the expression of the ideas of the supporters of collaboration and supporters of resistance, the consequences of the conference, the impact of the conference on subsequent political processes in Lithuania, and the activities of the National Council elected during the conference. In formal terms, the conference passed resolutions which were favourable for the Germans and which obligated Lithuanians to collaborate with Germany in its labour and military service structures. The key issue and objective, as well as a condition for collaboration, were Lithuania’s endeavour for sovereignty and mitigation of the effects of the German occupation of Lithuania. Some wordings reflecting this goal were included in the resolutions that were passed at the conference and that were subject to prior approval by the Germans. Such wording was not acceptable to the occupiers since it was not tolerant to Lithuania’s desire for sovereignty; therefore, the resolutions passed at the conference were amended following heavy pressure from officials of the occupying power. This means that the resolutions of the Lithuanian Conference that were published were not precise, authentic documents. The conference resulted only in some temporary, compromise-like phenomena in the policies of the German occupiers and in the avoidance of any open confrontation or repression. The resolutions of the conference did not have any decisive impact on the policies of the occupying power, in particular on the success of military mobilisation in Lithuania.
Keywords: Lithuania; German occupation; resistance; collaborants